Structured populations with diffusion in state space - Karl Peter Hadeler (Mathematical Biosciences and Engineering)
The classical models for populationsstructured by size have two features which may cause problems inbiologically realistic modeling approaches: the structure variablealways increases, and individuals in an age cohort that areidentical initially stay identical throughout their lives. Here adiffusion term is introduced in the partial differential equationwhich mathematically amounts to adding viscosity. This approachsolves both problems but it requires to identify appropriateboundary (recruitment) conditions. The method is applied tosize-structured populations, metapopulations, infectious diseases, and vector-transmitted diseases.